Indonesian Labor Protection through Social Employment Security in Sustainable Development Goals (SDGs) Perspective - Nur Hadiyati (Faculty of Law, Merdeka University Surabaya, Indonesia, 2021)
The goal of the Indonesian state is to improve people's welfare. This goal is further emphasized by developing a social security system for the welfare of all people. Fulfillment of socio-economic protection that is evenly distributed and does not differentiate between social groups must be carried out by the government because it contains the state ideology which states social justice for all people. To provide social security for all the people, especially workers, Indonesia has established Law Number 40 of 2004 concerning the National Social Security System. Based on this, this study aims to examine whether the existing social security system in Indonesia protects the people, especially workers, based on the perspective of Sustainable Development Goals (SDGs). The research method used in answering the problem is a normative legal research method with a statutory approach, a conceptual approach, and a historical approach. This research is expected to be able to contribute knowledge and literacy to society and academics related to labor protection. This research shows that labor social security is a form of protection provided to workers and their families against various labor market risks. From the SDGs perspective, the protection of workers through employment social security can reflect the SDGs Goal 8, namely decent work and economic growth, promoting sustainable and inclusive economic growth, employment, and decent work for all.